ANALYSIS OF COMPLETENESS OF CHILDBIRTH DOCUMENTATION IN THE TPMB IBI WORK AREA MADIUN REGENCY - Salsabila Reinsa Novy Nur Fitria; Eltigeka Devi Apriliani (PT. Radja Intercontinental Publishing, 2026)
Childbirth documentation is an essential component of midwifery services, functioning as legal evidence, a means of communication among health workers, the basis for clinical decision-making. Incomplete documentation is still frequently found in independent midwifery practices. This study aimed to analyze the completeness of childbirth documentation in the TPMB IBI work area Madiun Regency. The method used a quantitative descriptive. The population and sample consisted of 34 independent midwifery practices registered under IBI Madiun Regency, selected using total sampling. Research instruments included questionnaires and checklists. The results showed that most respondents were aged ≥36 years (82.4%), had a D4/S1 education level (94.1%), had established their TPMB for ≥10 years (61.8%), had good knowledge (85.3%), 50% had attended training. Analysis of the completeness level of delivery documentation based on staff capability (58.8%), material support (79.4%), method usage (70.6%), financial availability (76.5%). The completeness level of childbirth documentation was still relatively low, with only 55.9% categorized as complete. TPMB needs continuous practice, standard materials, financial support, implementation procedures, digitization of patient records to improve the quality of childbirth documentation.